Evaluating the Psychological Implications of the COVID-19 Pandemic Among Healthcare Workers: A Cross-Sectional Study - Wafaa S. Hamza; Ali Ghazi Almutairi; Lamiaa A. Ali (Advances in Public Health)
Conclusion: COVID-19 pandemic caused long-term psychological burden among HCWs. Further longitudinal researches are necessary to explore specific interventions to support HCWs’ mental health.